Oxide ion polarizability, optical basicity, and metallization criterion of GO-coated Nd2O3 (NPs) - TeO2 glass for linear optical fibre - Shaari, H. R.; Azlan, M. N.; Azlina, Y.; M. Al-Hada, N.; Umar, S. A.; Kenzhaliyev, B. K.; M. Zaid, M. H.; Hisam, R.; Yusof, N. N. (S.C. Virtual Company of Phisics S.R.L, 2022)
The versatility of graphene oxide (GO) as coating materials on the glass surface is a new revolution in the advanced glass era. In this work, GO liquid solution was prepared by using electrochemical exfoliation in an electrolyte solution assisted by different surfactants. Meanwhile, a glass series was prepared by using the conventional meltquenched technique. A low-cost and simple spray deposition technique was used to deposit the GO on the glass sample. The obtained glass series was denoted as GO coated TNd (NPs), meanwhile, the uncoated glass was labelled as uncoated TNd (NPs). The linear optical properties of GO coated TNd (NPs) glass series was determined using UVVis spectrophotometer and utilizing the Lorentz-Lorentz equation to determine the value of polarizability. X-ray diffraction spectra revealed the amorphous structural characteristics of the glass series. The SEM morphological image revealed the variation of GO distribution on the glass surface due to the agglomeration and inhomogeneity of GO distribution on the glass surface. The homogeneity of GO distribution on the glass surface is negligible in this work as we focus solely on the effect of GO on glass properties. According to the observations, the value of GO-coated TNd (NPs) is in the range 3.4531- 3.8549 Å and uncoated TNd (NPs) is in the range 2.709- 2.774 Å. Meanwhile, the optical basicity value ranges from 1.220 to 1.262. These results demonstrate that the polarizability of oxide ions and optical basicity values of the GO coated TNd (NPs) glass series was higher than the uncoated TNd (NPs) glass. The metallization criterion for the GO-coated TNd (NPs) glass system is in the range of 0.3 < M < 0.4. Based on these results, the obtained glasses are promising in linear optical glass fibre.